Nano-magnetic tunnel junctions controlled by electric field for straintronics. Issue 38 (16th August 2021) - Li, Peisen; Yao, Xinping; Hu, Yueguo; Pan, Mengchun; Ji, Minhui; Chen, Aitian; Peng, Junping; Qiu, Weicheng; Hu, Jiafei; Zhang, Qi; Piao, Hong-Guang; Zhang, Sen
Abstract : We integrated nanoscale MTJs on PMN-PT(011) ferroelectric substrates and investigated the magnetoresistance upon magnetic field and electric field. The obvious electric field control of resistance and chiral switching of nano-MTJ were demonstrated. Abstract : The magnetic tunneling junction (MTJ) controlled by electric field as an alternate approach for energy efficiency is the highlight for nonvolatile RAM, while there is still a lack of research on resistance manipulation with the electric field in nanoscale MTJs. In this study, we integrated nanoscale MTJs on the (011) orientated Pb(Mg1/3 Nb2/3 )0.7 Ti0.3 O3 (PMN-PT) ferroelectric substrates and systematically investigated the magnetoresistance as a function of the magnetic field and electric field. A single domain state of the nanoscale MTJ was demonstrated by the experimental result and theoretical simulation. Afterward, the obvious electric field control of R – H curves was obtained and explained by the competition between magnetoelastic energy and shape anisotropy. More importantly, simulation results also predicted that the switching pathway of magnetic moments under the magnetic field is strongly dependent on the applied electric field, displaying the electric field control of chiral switching in the nano-MTJ. Our work is a milestone in the realization of the emerging dubbed straintronics field.